Comparison of tris(2‐ethylhexyl) phosphate and di(2‐ethylhexyl) phosphoric acid toxicities in a rat 28‐day oral exposure study. Issue 5 (29th December 2019) - Pelletier, Guillaume; Rigden, Marc; Wang, Gen Sheng; Caldwell, Don; Siddique, Shabana; Leingartner, Karen; Kosarac, Ivana; Cakmak, Sabit; Kubwabo, Cariton
Abstract: Tris(2‐ethylhexyl) phosphate (TEHP, CAS no. 78‐42‐2) is a plasticizer and a flame retardant, while di(2‐ethylhexyl) phosphoric acid (DEHPA, CAS no. 298‐07‐7) is an oil additive and extraction solvent. Publicly‐available information on repeated exposure to these two related organophosphate compounds is fragmentary. Hence, adult male and female Fischer rats were exposed to TEHP (300, 1000 and 3000 mg/kg body weight [BW]/day) or DEHPA (20, 60 and 180 mg/kg BW/day) by gavage for 28 consecutive days, to assess and compare their toxicities. Although significantly impaired BW gains and evidence of TEHP enzymatic hydrolysis to DEHPA were observed only in males, exposures to the highest TEHP and DEHPA doses often resulted in similar alterations of hematology, serum clinical chemistry and liver enzymatic activities in both males and females. The squamous epithelial hyperplasia and hyperkeratosis observed in the non‐glandular forestomach of rats exposed to the middle and high DEHPA doses were most likely caused by the slightly corrosive nature of this chemical. Although tubular degeneration and spermatid retention were observed only in the testes of males exposed to the highest TEHP dose, numerous periodic acid‐Schiff stained crystalline inclusions were observed in testis interstitial cells at all TEHP dose levels. No‐observed‐adverse‐effect levels for TEHP and DEHPA are proposed, but the lower serum pituitary hormone levels resulting from TEHP and DEHPA exposures and the perturbations of testicular histology observed in TEHP‐treated males deserve further investigation. Improved characterization of the toxicity of flame retardants will contribute to better informed substitution choices for legacy flame retardants phased‐out over health concerns. Abstract : Tris(2‐ethylhexyl) phosphate (TEHP) is a plasticizer and a flame retardant, while the related di(2‐ethylhexyl) phosphoric acid (DEHPA) is an oil additive and extraction solvent. TEHP and DEHPA toxicities were compared in a rat 28‐day oral exposure study. Although TEHP hydrolysis to DEHPA was detected only in males, TEHP and DEHPA often had similar effects on the endpoints assessed in both males and females. The observed alterations of serum pituitary hormone levels and testis histological features in males warrant further investigation.